The Implementation of Internet of Things (IOT) In Education to Improve The Quality of Learning - Deitje Sofie Pogoh; Stevan Natanael Pinangkaan; Defen Eka Saputra Bawimbang; Douglas Jiferson Takaendengan; Jordan Kelvin Ladi; Matthew Torar (Syntax Corporation Indonesia, 2024)
The rapid development of the Internet of Things (IoT) has transformed various industries, and education is no exception. The implementation of IoT in education presents significant opportunities to enhance the quality of learning by creating interactive, connected, and personalized educational environments. This paper explores the potential benefits and challenges associated with integrating IoT technologies into educational systems. By leveraging smart devices, sensors, and real-time data, IoT can improve learning experiences, increase student engagement, and optimize classroom management. IoT-enabled solutions, such as smart classrooms, remote learning tools, and personalized learning pathways, provide real-time feedback and insights, helping educators track student progress and tailor instruction to individual needs. Additionally, IoT enhances collaboration and communication among students, educators, and educational institutions. However, the successful integration of IoT requires overcoming challenges related to infrastructure, security, and privacy concerns. This paper discusses the current trends in IoT applications in education, examines case studies, and provides recommendations for effectively implementing IoT to improve educational outcomes. Ultimately, the adoption of IoT has the potential to revolutionize learning by making it more interactive, efficient, and student-centered.